Detection of Virulence-Associated Genes Not Useful for Discriminating between Invasive and Commensal Staphylococcus epidermidis Strains from a Bone Marrow Transplant Unit - Rohde, Holger (American Society for Microbiology, 2004)
Because of their biofilm-forming capacity, invasive Staphylococcus epidermidis isolates, which cause the majority of nosocomial catheter-related bloodstream infections (BSIs), are thought to be selected at the time of catheter insertion from a population of less virulent commensal strains. This fact allows the prediction that invasive and contaminating strains can be differentiated via detection of virulence-associated genes. However, the hospital environment may pave the way for catheter-related infections by promoting a shift in the commensal bacterial population toward strains with enhanced virulence. The distribution of virulence-associated genes (icaADBC, aap, atlE, bhp, fbe, embp, mecA, IS256, and IS257), polysaccharide intercellular adhesin synthesis, and biofilm formation were investigated in S. epidermidis strains from independent episodes of catheter-related BSIs in individuals who have received bone marrow transplantation (BMT). The results were compared with those obtained for commensal S. epidermidis isolates from hospitalized patients after BMT and from healthy individuals, respectively. The clonal relationships of the strains were investigated by pulsed-field gel electrophoresis. icaADBC, mecA, and IS256 were significantly more prevalent in BSI isolates than in commensal isolates from healthy individuals. However, the prevalence of any of the genes in clonally independent, endogenous commensal strains from BMT patients did not differ from that in invasive BSI strains. icaADBC and methicillin resistance, factors important for the establishment of catheter-related infections, already ensure survival of the organisms in their physiological habitat in the hospital environment, resulting in a higher probability of contamination of indwelling medical devices with virulent S. epidermidis strains. The dynamics of S. epidermidis populations reveal that detection of icaADBC and mecA is not suitable for discriminating invasive from contaminating S. epidermidis strains.